2008
DOI: 10.1152/ajpregu.90400.2008
|View full text |Cite
|
Sign up to set email alerts
|

Development of the ACTH and corticosterone response to acute hypoxia in the neonatal rat

Abstract: Acute episodes of severe hypoxia are among the most common stressors in neonates. An understanding of the development of the physiological response to acute hypoxia will help improve clinical interventions. The present study measured ACTH and corticosterone responses to acute, severe hypoxia (8% inspired O(2) for 4 h) in neonatal rats at postnatal days (PD) 2, 5, and 8. Expression of specific hypothalamic, anterior pituitary, and adrenocortical mRNAs was assessed by real-time PCR, and expression of specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 64 publications
11
51
0
Order By: Relevance
“…We have previously shown that acute, continuous hypoxia resulted in a pituitary-adrenal response in neonatal rats (4). In the present study, IH elicited a large increase in ACTH and an associated increase in corticosterone in older animals.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…We have previously shown that acute, continuous hypoxia resulted in a pituitary-adrenal response in neonatal rats (4). In the present study, IH elicited a large increase in ACTH and an associated increase in corticosterone in older animals.…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, IH elicited a large increase in ACTH and an associated increase in corticosterone in older animals. These responses represented an adult-type, ACTH-dependent increase in corticosterone in response to stress (4). Interestingly, the corticosterone response to IH in PD2 rats was the greatest in magnitude but was associated with a very small increase in plasma ACTH.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Studies in rats and pikas and ewes, exposed to altitude mediate reduced oxygen breathing suggested that hypoxic stress increases release of ACTH via cAMP (4,20). Acute hypoxia seems also to result in increased ACTH release and cortisone blood levels in neonatal rats (21). Intermitent hypoxia has been also shown to suppress GH mRNA expression in adenohypophysis and of GH release in rats (22).…”
Section: Figure 1 Immunohistochemical Staining Of Tissue Sections: (mentioning
confidence: 99%